2023
DOI: 10.3390/cryst13050800
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure of Manganotychite, Na6Mn2(CO3)4(SO4), and Structural Relations in the Northupite Group

Abstract: The crystal structure of manganotychite has been refined using the holotype specimen from the Alluaiv Mountain, Lovozero massif, Kola peninsula, Russia. The mineral is cubic, Fd3¯, a = 14.0015(3) Å, V = 2744.88(18) Å3, Z = 8, R1 = 0.020 for 388 independently observed reflections. Manganotychite is isotypic to tychite and ferrotychite. Its crystal structure is based upon a three-dimensional infinite framework formed by condensation of MnO6 octahedra and CO3 groups by sharing common O atoms. The sulfate groups a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In addition to mixed polyanionic materials presented, a less studied mineral, Na 6 Mg 2 (CO 3 ) 4 SO 4 , called tychite, can be considered. Tychite belongs to the northupite group, where its analogues ferotychite Na 6 Fe 2 (CO 3 ) 4 SO 4 20 and manganotychite Na 6 Mn 2 (CO 3 ) 4 SO 4 21 are also found. The first mention of tychite was made by S. L. Penfield and G. S. Jamieson 22 during the study of northupite Na 3 Mg(CO 3 ) 2 Cl found in Lake Borax, California.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to mixed polyanionic materials presented, a less studied mineral, Na 6 Mg 2 (CO 3 ) 4 SO 4 , called tychite, can be considered. Tychite belongs to the northupite group, where its analogues ferotychite Na 6 Fe 2 (CO 3 ) 4 SO 4 20 and manganotychite Na 6 Mn 2 (CO 3 ) 4 SO 4 21 are also found. The first mention of tychite was made by S. L. Penfield and G. S. Jamieson 22 during the study of northupite Na 3 Mg(CO 3 ) 2 Cl found in Lake Borax, California.…”
Section: Introductionmentioning
confidence: 99%